Prenatal Diagnosis of Aorta-Porto-Umbilical Vein Fistulas with Left-Sided Inferior Vena Cava - Zhou, Jiawei; Zhou, Qichang; Peng, Qianghai; Zeng, Shi (American Journal of Perinatology Reports, 2016)
Congenital arteriovenous fistulas involved with the abdominal aorta are very rare. Left-sided subrenal inferior vena cava (IVC) with normal connection to the heart is also rare and has not been reported prenatally. In this article, we described a fetus with aorta-porto-umbilical vein fistulas combined with a left-sided IVC.
Keywords: fetal; fistulas; left-sided inferior vena cava